IMPACT ANALYSIS OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEE PERFORMANCE - Shinta Widia Ningrum; Dilla Amalia; Ecep Supriatna (Journal of Public Administration, 2022)
This study aims to analyze the influence of transformational leadership on the performance of public employees in a government agency. The survey method is used to collect data from employees who are the research subjects. Statistical analysis, including regression, was used to identify the relationship between transformational leadership and employee performance. The results of the research show that there is a positive and significant influence between transformational leadership and the performance of public employees. Employees who experience transformational leadership tend to show higher levels of performance, including achievement of work targets, initiative, collaboration, and better job satisfaction. This research indicates the importance of transformational leadership in improving public employee performance and offers important implications for the development of transformational leadership in the context of government